Negative capability? Measuring the unmeasurable in education. Issue 1 (2nd January 2017) - Unterhalter, Elaine
ABSTRACT: This introductory article to the special issue of Comparative Education on measuring the unmeasurable in education considers measurement as reflecting facts and uncertainties. The notion of negative capability is used metaphorically to depict some limits of what is measurable, and portray aspects of the process of education, associated with uncertainty and public scrutiny of complexity. Four overarching questions – what, when, why and how – have guided the reflections of the authors who have contributed to the special issue. What are we measuring when we try to measure the unmeasurable in education and what are we not measuring? When have attempts been made to measure the unmeasurable in education, what metrics have been adopted in which contexts, and with what outcomes? Why have measures been adopted as indicators of the unmeasurable, such as human rights? How have particular historically located organisations approached the problem of measuring the apparently unmeasurable in education, with what epistemological, normative and conceptual resources, and consequences? The introductory article looks at measurement as a form of negative capability in some discussions of history of social statistics in education, the current debate over indicators for the Sustainable Development Goals, and how to measure gender equality in education.